Capturing Community Participation in Rural Tourism through PRA: A Study in Meghalaya - Sai Priyanka, Pagadala; Devarani, Loukham (Indian Journal of Extension Education, 2022)
Rural tourism as an agri-business enterprise has potential for socio-economic development of rural area and yields numerous benefits to strengthen culture, livelihood and technological outlook of communities, for which sustainability in the development venture depends on community participation. The study was taken up in two popular rural tourism centers viz., Mawlynnong (cleanest village of Asia) and Sohliya (Strawberry village) of Meghalaya state that has heavy tourist traffic; to carry out community stakeholder analysis of rural tourism. Through key informant technique, personal interview and observation, 15 categories of community stakeholders were identified. This was followed by a community level meeting of the key stakeholders and few residents in each tourism center where PRA exercises were conducted for information generation and discussion. It was found that community stakeholders organize rural tourism for various reasons through various means  The village council (Dorbar Shong) performed multiple roles and had high influence in village. Efforts in mobilizing community to undertake homestays and dhabas, emphasis on creation of exclusive tourism cooperatives within village to coordinate vital activities between stakeholders may ensure effective and sustainable participation by community members.
Keywords: Community participation; Rural livelihood; Rural tourism; Stakeholders